Investigation of pore structure and fractal characteristics of marine-continental transitional shales from Longtan Formation using MICP, gas adsorption, and NMR (Guizhou, China). (September 2019) - Ma, Xiao; Guo, Shaobin; Shi, Dishi; Zhou, Zhi; Liu, Guoheng
Abstract: Organic-rich shale samples from marine-continental transitional facies of the Late Permian Longtan Formation in southwestern Guizhou were investigated using organic petrography analysis, X-ray diffraction analysis, mercury intrusion capillary pressure experiments, gas adsorption experiments, nuclear magnetic resonance, scanning electron microscopy image analysis, and multi-fractal theory to quantitatively and qualitatively investigate the full-size pore structure and fractal characteristics of the shale. The correlations among the total organic carbon (TOC) content, mineral composition, and pore structure were discussed. The fractal dimension was used to evaluate the production potential of a shale reservoir. Results show that samples have a high TOC content (4.38 wt % on average), low permeability (less than 0.001 mD), and complex pore structure. The pore volume (PV) varies from 0.001997 cm 3 /g to 0.03653 cm 3 /g, with an average of 0.02864 cm 3 /g, and the specific surface area (SSA) varies from 14.144 m 2 /g to 29.740 m 2 /g, with an average of 21.533 m 2 /g. Mesopores (diameter between 2 and 50 nm according to IUPAC) are the predominant contributors to the pore volume, while mesopores and micropores (diameter less than 2 nm) are the main contributors to the specific surface area. The shale samples with higher TOC and clay mineral content have larger PVs and SSAs and higher fractal dimensions than those that do not. A high fractal dimension indicates a rough pore surface and complicated pore structure. Shale with higher D1 and DA (representing the pore surface roughness and the adsorption space, respectively) has high adsorption capacity and favors gas accumulation, while shale with higher D2 and DS (representing the pore structure complexity and the seepage space, respectively) has greater flow capability and favors gas diffusion. Highlights: Quantitative methods were combined with qualitative methods in this study to investigate the full-size pore structure characteristics of marine-continental transitional shale. The fractal characteristics of transitional Longtan shale were investigated using multi-fractal concept and different experiments. The fractal dimension was used to evaluate the production potential of shale reservoir.